Letter (copy) : Scottish Trade Union food ship for Spain - Citrine, Walter, 1887-1983
030-0035-001 International. WMC/EAB/AT/20 11th October, 1938 Mr. W. Schevenels, International Federation of Trade Unions, 9 Avenue D'Orsay, Paris, 7. Dear Comrade Schevenels, SCOTTISH TRADE UNION FOOD SHIP FOR SPAIN With further reference to our letter of the 20th September regarding the shipment of a consignment of goods to Valencia, we are now able to inform you that the steamer which is conveying these goods is the S.S. Stangate. Owing to certain difficulties, the steamer was unable to keep to her schedule, but we now learn that she will be leaving Glasgow tomorrow, Wednesday, 12th instant, and we shall be glad if you will advise our Spanish comrades accordingly. Yours sincerely, General Secretary. 292/946/30/35